La Space conceptualization: Language and cognitive egocentrism - Calderón Guerrero, Gabriela (Consorcio de Universidades Mexicanas A.C., 2020)
The conceptualization of space and its communicability to other human beings are essential for human survivial and the genesis and support of culture (Piaget and Inhelder, 2015; Chatterjee, 2001). This study analyzes how the participants solved a task that involves the conceptualization of space, in which it was requested to describe the spatial location of a series of objects to another person. 60 mexican children and adolescents organized in three different age groups (9-10, 11-12 and 13-14 years) were interviewed. The investigation consisted in two phases. In the first one, a diagnostic test of inclusion was carried out to ensure that participants were not disadvantaged in the knowledge of left and rigth locations according to their age. In the second phase the task of “Scene description” was performed. The analysis of the data indicates a systematic difference in the conceptualization of the space between children of different groups, reflected by a statistically significant difference in the variable “type of linguistic construction”. The findings make it possible to verify that the descriptions of the participants are increasingly precise, since they provide more and better information to other person. This work also provides cualitative information. Finally, this study show the usefulness of linguistic analysis to describe, to quantify and to study  the conceptualization of space and its relation with the overcoming of cognitive egocentrism, that is, it is usefulness in analyzing the development of intelligence.